A Globally Significant Potential Megascale Geopark : The Eastern¬†Australian Mantle Hotspot Interacting with a North-Migrating Heterogeneous Continental Plate Creating a Variety of Volcano Types, Magmas, Xenoliths, and Xenocrysts - Brocx, Margaret (2022)
Australia commenced separating from Antarctica some 85 million years ago, finally separating about 33 million years ago, and has been migrating northwards towards the Eurasian plate during that time. In the process, Australia, on its eastern side, progressively passed over a mantle hotspot. A magma plume intersected a variable lithocrust with various lithologic packages such as Phanerozoic sedimentary basins, fold belts and metamorphic terranes, and Precambrian rocks. As such, there was scope for compositional evolution of magmas through melting and assimilation, as well as plucking of host rocks to include xenoliths, and xenocrysts. The volcanic chain, volcanoes, and lava fields that are spread latitudinally along 2000¬†km of eastern Australia present a globally-significant volcanic system that provides insights into magma and crust interactions, into the variability of xenoliths and xenocrysts, into magma evolution dependent on setting, and into the mantle story of the Earth. The Cosgrove Volcano Chain is an example of this, and stands as a globally-unique potential megascale geopark.